THE INFLUENCE OF GREEN PLACE, GREEN PRODUCT, AND GREEN PROMOTION ON INTEREST IN BUYING ENVIRONMENTALLY FRIENDLY PRODUCTS - M Hafis Alwi; Sari, Herlinda Maya Kumala (International Journal Multidisciplinary (IJMI), 2025)
Objective: This research aims to determine the influence of green places, green products, and green promotion on interest in purchasing environmentally friendly products. The main problem in this research is the large amount of plastic use which causes the ecosystem to be polluted due to the actions of humans who do not care about the environment. Method: The research uses quantitative methods. The sampling technique used is probability sampling, using the Random Sampling method. In calculations using the Cochran Formula, the result was 96.04, so the minimum number was 96 samples from people who live in Sidoarjo. The analytical tools used in this research are validity test, reliability test, classical assumption test, multiple linear regression analysis, hypothesis testing t test, R test, R2 test using the SPSS version 22 application program. Results: The results of this research prove that green place has a significant effect on buying interest. Green products have a significant effect on buying interest. green promotion has a significant effect on purchasing interest. The three variables simultaneously have a significant effect on buying interest. Novelty: The main problem in this research is the large amount of plastic use which causes the ecosystem to be polluted due to the actions of humans who do not care about the environment.